Adult Hippocampal Neurogenesis in Parkinson's Disease: Impact on Neuronal Survival and Plasticity. (3rd July 2014) - Regensburger, Martin; Prots, Iryna; Winner, Beate
Abstract : In Parkinson's disease (PD) and other synucleinopathies, chronic neurodegeneration occurs within different areas of the central nervous system leading to progressive motor and nonmotor symptoms. The symptomatic treatment options that are currently available do not slow or halt disease progression. This highlights the need of a better understanding of disease mechanisms and disease models. The generation of newborn neurons in the adult hippocampus and in the subventricular zone/olfactory bulb system is affected by many different regulators and possibly involved in memory processing, depression, and olfaction, symptoms which commonly occur in PD. The pathology of the adult neurogenic niches in human PD patients is still mostly elusive, but different preclinical models have shown profound alterations of adult neurogenesis. Alterations in stem cell proliferation, differentiation, and survival as well as neurite outgrowth and spine formation have been related to different aspects in PD pathogenesis. Therefore, neurogenesis in the adult brain provides an ideal model to study disease mechanisms and compounds. In addition, adult newborn neurons have been proposed as a source of endogenous repair. Herein, we review current knowledge about the adult neurogenic niches in PD and highlight areas of future research.